Mechanisms of abscisic acid-mediated control of stomatal aperture - Munemasa, Shintaro; Waadt, Rainer (Current opinion in plant biology, 2015)
Drought stress triggers an increase in the level of the plant hormone abscisic acid (ABA), which initiates a signaling cascade to close stomata and reduce water loss. Recent studies have revealed that guard cells control cytosolic ABA concentration through the concerted actions of biosynthesis, catabolism as well as transport across membranes. Substantial progress has been made at understanding the molecular mechanisms of how the ABA signaling core module controls the activity of anion channels and thereby stomatal aperture. In this review, we focus on our current mechanistic understanding of ABA signaling in guard cells including the role of the second messenger Ca2+ as well as crosstalk with biotic stress responses.